"There's Always Next Year": Primary Care Team and Parent Perspectives on the Human Papillomavirus Vaccine. Issue 8 (2nd August 2020) - Dang, Julie H. T.; Stewart, Susan L.; Blumberg, Dean A.; Rodriguez, Hector P.; Chen, Moon S.
ABSTRACT: Acceptance of the human papillomavirus (HPV) vaccination among parents and clinicians is high, but uptake remains low. Little is known about organizational and primary care team factors that influence the uptake of the HPV vaccine. Interviews with clinicians, clinic support staff, and parents of adolescent patients were conducted to better understand the interrelationships among the people and the organizational processes that influence HPV vaccine uptake at the point of care. Between July 2016 and February 2017, semi-structured interviews of 40 participants (18 clinicians, 12 clinic support staff, and 10 parents of adolescent patients) in a primary care network were conducted. Organizational structures and processes, such as electronic provider reminders, availability of "vaccination only" appointments, and knowledgeable primary care team members contributed to HPV vaccine uptake. Consistently high support of HPV vaccination was found among key informants; however, rather than refuse HPV vaccination, parents are opting to delay vaccination to a future visit. When parents express the desire to delay, clinicians and care team members described often recommending addressing HPV vaccination at a future visit, giving parents the impression that receiving the vaccine was not time-sensitive for their child. Discordance in HPV vaccination recommendations among providers and clinic support staff may contribute to delayed HPV vaccination. Strong, high-quality HPV vaccine recommendations are needed from all primary team members. Clinic interventions to accelerate HPV vaccine uptake may benefit from a team-based approach where every member of the primary care team is delivering the same consistent messaging about the importance of timely HPV vaccination.